Easy Ways to Learn English Language - Abduvoitov Ravshanbek Alijonovich (Zien Journals, 2021)
In this article, we will discuss ideas for easy English grammar learning, the implementation of English vocabulary, in particular through actions in teaching verbs, Listening Comprehension, and the usefulness of mobile applications that teach English.
Keywords: English; grammatic; mobile applications; vocabulary